Selecting the Optimal Location for a New Facility: A PROMETHEE II Analyst - Harjanti, Trinugi Wira; Widjaja, Herry Rachmat; Nofirman, N; Sudipa, I Gede Iwan; Pramono, Susatyo Adhi; Rahim, Robbi (Universitas Dharma Wacana, 2023)
This paper presents a case study of location selection for a new facility using the multi-criteria decision making (MCDM) method, PROMETHEE II. The PROMETHEE II method is a widely used method for solving problems that involve multiple criteria and alternatives. The method allows for the ranking of alternatives based on their overall net flow, which is calculated by weighting and comparing the criteria values for each pair of alternatives. The case study evaluated five different locations based on criteria such as access to transportation, availability of skilled labor, and cost of living. The results of the analysis indicate that C1 was ranked as the most attractive location, with the highest scores for all criteria and the highest overall net flow among all alternatives. A sensitivity analysis was performed to ensure that the results were robust and not sensitive to small changes in the weight of the criteria. The results of this study demonstrate the utility and effectiveness of the PROMETHEE II method in practice and provide valuable insights for further research and practical action.